Notoemys zapatocaensis, a new side-necked turtle (Pleurodira: Platychelyidae) from the early cretaceous of Colombia (2005)
A carapace and posterior plastral lobe from the early Cretaceous Valanginian of northeastern Colombia is a new species of the pleurodire Notoemys. It is a pleurodire based on the sutured pelvis and xiphiplastral notch. Notoemys zapatocaensis, n.sp., differs from the other two species of Notoemys, N. oxfordiensis and N. laticentralis, in having a slightly serrated posterior margin, a very small third peripheral, no contact of costal 1 and peripheral 3, and protuberances developed on the pleural and vertebral scale areas. Notoemys zapatocaensis, n.sp., extends the distribution of Notoemys from Argentina and Cuba to Colombia geographically, and from the 156 mya Oxfordian late Jurassic to the 135 mya Valanginian early Cretaceous. Reanalysis based on morphology of the new shell suggests that Notoemys is the sister taxon to the late Jurassic European Platychelys based on the common possession of a very large costovertebral tunnel, tubercle on anterior margin of first thoracic rib, wide, flat thoracic ribs, and a first thoracic centrum that is wider than high.